Analisis Studi Peristiwa Invasi Rusia ke Ukraina terhadap Harga Saham IDX 80 di Bursa Efek Indonesia (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This research was conducted to analyze the impact of Russia’s invasion of Ukraine, as well as its reaction to companies listed on the IDX 80 index on the Indonesia Stock Exchange. Trading Volume Activity (TVA) and Security Return Variability (SRV) are the variables used to analyze the reactions. The test was conducted for five days before and after the invasion on February 24, 2022 using the Wilcoxon signed rank test. After statistical testing was conducted, there was a difference in the average TVA before and after the event. This indicates that the market reacted to the Russian invasion of Ukraine. In contrast, SRV did not show a difference in average before and after the Russian invasion of Ukraine. This condition is caused by information uncertainty or asymmetric information dissemination. This uncertainty results in not all investors having enough information to make decisions that will benefit investors due to an event. In addition, investors also lack the necessary knowledge to make decisions about their investments that are not supported by proper information dissemination.